Transcriptome and metabolome analysis of flavonol synthesis in apricot fruits - Han, Xueping; Wang, Jinzheng; Wang, Guiping; Dong, Fang; Nie, Peixian; Xue, Xiaomin (Frontiers in Plant Science, 2023)
Introduction Apricot fruits are edible and serve as a source of medicinal compounds. Flavonols are important plant secondary metabolites that have antioxidant and antitumor effects and may promote cardiovascular health. Methods The flavonoid content in three stages of the ‘Kuijin’ and the ‘Katy’ was observed, followed by the combination of metabolome and transcriptome analysis to explore the metabolic basis of flavonol synthesis. Results The differences in the metabolite contents between stages (of the same cultivar) and between cultivars (at the same stage) revealed decreases in the flavonoid content as fruits developed (i.e., from 0.28 mg/g to 0.12 mg/g in ‘Kuijin’ and from 0.23 mg/g to 0.05 mg/g in ‘Katy’). To decipher the regulation of flavonol synthesis in apricot (Prunus armeniaca L.), the metabolomes and transcriptomes of fruit pulp at three developmental stages of ‘Kuijin’ and the ‘Katy’ were analyzed. A total of 572 metabolites were detected in ‘Kuijin’ and the ‘Katy’ pulp, including 111 flavonoids. The higher flavonol content young ‘Kuijin’ fruits at 42 days after full bloom is mainly due to 10 types of flavonols. Three pairs of significant differences in flavonol content were identified. From these three comparison groups, three structural genes were strongly correlated with the levels of 10 types of flavonols (Pearson correlation coefficients > 0.8, p value < 0.05), including PARG09190, PARG15135, and PARG17939. The weighted gene co-expression network analysis showed that the turquoise module genes were highly correlated with flavonol contents (P < 0.01). There were 4897 genes in this module. Out of 4897 genes, 28 transcription factors are associated with 3 structural genes based on weight value. Two of the transcription factors are not only associated with PARG09190 but also with PARG15135, indicating their critical importance in the flavonols biosynthesis. The two TFs are PARG27864 and PARG10875. Discussion These findings provide new insights into the biosynthesis of flavonols and may explain the significant differences in flavonoid content between the ‘Kuijin’ and the ‘Katy’ cultivars. Moreover, it will aid in genetic improvement to enhance the nutritional and health value of apricots.